MEDIA SOSIAL, KUALITAS TIDUR, DAN AGRESIVITAS MAHASISWA DI ERA DIGITAL - Cholifah, Nur; Rini, Amanda Pasca; Pratitis, Nindia (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2025)
College students are in the developmental phase of late adolescence to early adulthood, a period that is vulnerable to emotional, social, and academic pressure. This condition places students at risk of experiencing emotional disturbances, such as aggressiveness. Along with technological advancement, students are increasingly exposed to high social media usage and irregular sleep patterns, both of which are suspected to affect emotional stability and aggressive behavior. The goal of this study is to find out how the amount of time university students in Surabaya spend on social media affects their sleep quality and aggressiveness. Because the data didn't meet the assumptions for linierity, this study used a correlational quantitative approach with Spearman's rank correlation test. There were 310 students in the study, and they were chosen through snowball sampling. The social media usage intensity scale, sleep quality scale, and aggressiveness scale were all used. All of these scales had passed tests for validity and reliability. The results showed that how much someone used social media did not have a strong link to how aggressive they were (r = 0.027; p = 0.638). On the other hand, how well someone slept did have a strong negative link to how aggressive they were (r = -0.491; p < 0.01). Students with poor sleep quality tended to exhibit higher levels of aggressiveness. This study concludes that improving sleep quality can serve as a preventive strategy to reduce student aggressiveness. ABSTRAK Mahasiswa tergolong masa remaja akhir dan transisi menuju awal masa dewasa yang rentan terhadap tekanan emosional, sosial, dan akademik. Kondisi tersebut menjadikan mereka berisiko mengalami gangguan emosi seperti agresivitas. Seiring perkembangan teknologi, penggunaan media sosial yang tinggi dan pola tidur yang terganggu menjadi bagian dari gaya hidup mahasiswa, yang diduga memengaruhi kestabilan emosi dan kecenderungan perilaku agresif. Penelitian ini bertujuan untuk mengetahui hubungan antara intensitas penggunaan media sosial dan kualitas tidur dengan agresivitas pada mahasiswa di Surabaya. Metode yang digunakan adalah kuantitatif korelasional dengan teknik analisis Spearman karena data tidak memenuhi asumsi linieritas. Subjek berjumlah 310 mahasiswa yang diperoleh melalui teknik snowball sampling. Instrumen yang digunakan adalah skala intensitas penggunaan media sosial, skala kualitas tidur, dan skala agresivitas, yang telah diuji validitas dan reliabilitasnya. Hasil menunjukkan tidak ada hubungan signifikan antara intensitas penggunaan media sosial dan agresivitas (r = 0,027; p = 0,638), namun terdapat hubungan negatif signifikan antara kualitas tidur dan agresivitas (r = -0,491; p < 0,01). Mahasiswa dengan kualitas tidur buruk cenderung menunjukkan agresivitas lebih tinggi. Penelitian ini menegaskan bahwa peningkatan kualitas tidur dapat menjadi strategi efektif untuk menekan agresivitas mahasiswa.